Trace metals and polycyclic aromatic hydrocarbons in the Eastern Mediterranean sediments: Concentration ranges as a tool for quality control of large data collections. (December 2022) - Lipizer, M.; Berto, D.; Cermelj, B.; Fafandjel, M.; Formalewicz, M.; Hatzianestis, I.; Ilijanić, N.; Kaberi, H.; Kralj, M.; Matijevic, S.; Molina Jack, M.E.; Parinos, C.; et al.
Abstract: Assessing the status of marine pollution at regional and sub-regional scales requires the use of comparable and harmonized data provided by multiple institutions, located in several countries. Standardized data management and quality control are crucial for supporting a coherent evaluation of marine pollution. Taking the Eastern Mediterranean Sea as a case study, we propose an approach to improve the quality control procedures used for sediment pollution data, thus supporting a harmonized environmental assessment. The regional ranges of contaminant concentrations in sediments were identified based on an in-depth literature review, and the lowest measured concentrations were evaluated to determine the "background concentrations" of chemical substances not yet targeted in the Mediterranean Sea. In addition, to verify the suitability of the approach for validating large data collections provided by multiple sources, the determined ranges were used to validate a regional dataset available through EMODnet data infrastructure. Highlights: Trace metal and PAH concentration ranges in the Eastern Mediterranean Review of coastal and offshore sediment contaminant concentration ranges Data validation for regional and sub-regional pollution assessment Background concentrations for priority substances in Mediterranean sea sediments